A review on modeling of flexible deformable object for dexterous robotic manipulation - Hou Y.C.; Sahari K.S.M.; How D.N.T. (SAGE Publications Inc., 2023)
Computer vision; Object detection; Robotics; Virtual reality; Deformable modeling; Deformable object; Deformable object modeling; Dexterous manipulation; Manipulation strategy; recognition and manipulation; Robotic controls; Robotic manipulation; Deformation